MENINGKATKAN LITERASI DAN MINAT BACA ANGGOTA TAMAN BACA ABDUROHMAN - Novy Trisnani; Wulan Tri Puji Utami (LPPM Universitas Trunojoyo Madura, 2022)
This service activity is a collaboration between the Service Team and Taman Baca Abdurohman. Taman Baca Abdurohman at the beginning of its establishment was the initiation of a community group in RT.13/08 Panjatan, Kulon Progo. The purpose of establishing the Taman Baca Abdurohman is to facilitate children in the surrounding environment who like to read or want to read but are hindered by economic affordability. In addition, the purpose of establishing the Taman Baca Abdurohman is to increase interest in reading and improve literacy, especially for children around and in general the community in the reading park environment is located. Children as the main users of the benefits of Taman Baca Abdurohman's have a tendency to like folklore and fairy tales. With the advancement of science and technology, of course, adjustments must be made by Taman Baca Abdurohman. The service team and partner cooperation programs implemented to achieve these goals are empowerment and mentoring. Empowerment activities are carried out through adding to the collection of books in Abdurohman's reading park and implementing empowerment for PKK mothers around the reading park locations, mentoring activities are carried out through the provision of English language tutoring and competitions. The results of the evaluation of the service program showed that there was an increase in the number of visits by members of the Taman Baca Abdurohman and the general public to the place. So it can be concluded that the solution provided by the service team is appropriate to overcome the problems that exist in Taman Baca Abdurohman's.